THE SHIFTING SANDS OF REALITY: POWER, SUBJECTIVITY AND THE MECHANISMS OF CONTROL IN HARI KUNZRU’S RED PILL - Malik, Sonia (International Journal of Research -GRANTHAALAYAH, 2025)
This paper explores Red Pill (2020) by Hari Kunzru as a novel that reflects the growing concerns of a dystopian world shaped by technology, misinformation and surveillance. Using close reading as its methodology, the study examines how Kunzru’s use of the “red pill” metaphor critiques the allure of ideological extremism, particularly within the context of alt-right discourse. As part of Kunzru’s color trilogy—alongside White Tears (2017) and Blue Ruin (2024)—Red Pill reflects the fractured nature of modern identity and the psychological consequences of ideological entrapment in a divided world. The story follows an unnamed protagonist who, drawn into the world of alt-right ideology, begins to lose touch with reality, embodying the anxieties of a postmodern society where truth is constantly questioned. By portraying the protagonist’s psychological breakdown, the novel highlights the dangers of living in an era where technology and media control our understanding of the world. The book critiques how dystopian forces, such as political extremism and the search for false truths, shape our lives in a postmodern age marked by uncertainty and fragmentation. Divided into four sections—Wannsee, Zersetzung, An Apocalypse, and Home—the novel interrogates key socio-political tensions in Europe and the USA at the turn of the 21st century, exploring themes of identity, freedom, and collective consciousness in a media-dominated society. Red Pill deconstructs the red pill as a symbol of supposed enlightenment, revealing how the pursuit of meaning in an era of misinformation and surveillance leads to existential fragmentation. Overall, this study provides insight into how Kunzru’s narrative critiques the intersection of technology, authoritarianism, and personal freedom, suggesting that the digital age, rather than providing liberation, often subjects individuals to new forms of control.